2023
DOI: 10.7759/cureus.33695
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital and Alcohol Withdrawal Syndrome: A Systematic Review and Meta-Analysis

Abstract: Alcohol withdrawal syndrome (AWS) is a complication frequently encountered among patients who are chronic alcohol abusers. It is considered to have a significant impact on the United States healthcare system.It not only has a toll on the healthcare spending but also contributes to significant morbidity and mortality. Benzodiazepines are considered first line in the treatment of AWS. Since patients with alcohol use disorder have downregulated gamma aminobutyric acid (GABA) receptors, this often leads to benzodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Importantly, combination therapy was not associated with additional adverse events, while multiple studies reported adverse events associated with benzodiazepine monotherapy. These findings are consistent with those of prior reviews, which have also found combination therapy to have some potential benefits in treating AWS over benzodiazepine monotherapy, particularly in more severe cases of AWS 42–45 . The prior reviews focus on ICU settings or were conducted prior to the current review.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, combination therapy was not associated with additional adverse events, while multiple studies reported adverse events associated with benzodiazepine monotherapy. These findings are consistent with those of prior reviews, which have also found combination therapy to have some potential benefits in treating AWS over benzodiazepine monotherapy, particularly in more severe cases of AWS 42–45 . The prior reviews focus on ICU settings or were conducted prior to the current review.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with those of prior reviews, which have also found combination therapy to have some potential benefits in treating AWS over benzodiazepine monotherapy, particularly in more severe cases of AWS. [42][43][44][45] The prior reviews focus on ICU settings or were conducted prior to the current review.…”
Section: Discussionmentioning
confidence: 99%
“…No patients in the case series PB cohort ( n = 33) developed AW or AE compared to other literature, where 48% and 19% of patients developed AW or AE in the cohort ( n = 52), respectively 12 . A recent meta‐analysis demonstrated a similar decrease in hospital LOS with PB usage compared to BZD usage 13 …”
Section: Discussionmentioning
confidence: 67%
“…12 A recent meta-analysis demonstrated a similar decrease in hospital LOS with PB usage compared to BZD usage. 13 In this case series, three patients returned to the ED within a short duration of time after PB administration. All patients had been instructed not to drive or drink alcohol for at least 7 days after receiving PB.…”
Section: Discussionmentioning
confidence: 72%
“…One meta-analysis that compared PB with lorazepam for treatment of AWS in an ICU setting showed a reduction in the length of hospital stay by 2.6 days in favor of PB. Still, the study was limited due to the lack of uniformity or a standardized phenobarbital dosing regimen across different studies [28]. Another study that compared PB with BDZs for AWS in an ICU setting demonstrated a decreased duration of AWS and ICU LOS without differences in hospital LOS or adverse events [29].…”
Section: Discussionmentioning
confidence: 99%